Estratégias de valoração dos produtos agroindustriais das mulheres rurais do Assentamento Nova Amazônia em Roraima através do registro de marca coletiva - Gadelha, Liliane Barbosa dos Santos (2021)
This study aims to present strategies for valuing the agro-industrial products of rural women of the Association of Rural Workers in the Family Regime of the Nova Amazônia I - ASSTRF - PANA Settlement Project, with a view to exploring managerial characteristics to overcome the limitations of access to the market of products originating from family farming, as well as describing the importance of trademark registration for the valuation of agri-food products of rural women of the Nova Amazônia Settlement project in Roraima, presenting a diagnosis to verify the main strengths, opportunities, weaknesses and threats for insertion of rural women's products in the market. In addition to collectively developing the brand and its usage regulations in order to promote the recognition of this production. The methodology adopted was exploratory research to bibliographic references, to form the foundations that guided the characterization of the activity and the background of the study area. It was also contextualized, the antecedents of productive inclusion of women in agriculture. The research activities were developed through the focus group methodology, with collective meetings and the participation of women from the association with the objective of recording the information presented by the producers and applying it to the analysis of the SWOT matrix. The technological product of this study was built with the effective participation of the producers, contributing to the elaboration of the regulation that establishes the conditions of use of the collective mark and the formalization of the request for registration of the collective mark of products of the agro-industrial enterprise of rural women. It is expected that the regulation and trademark registration will be an alternative for adding value to the agro-industrial products of these rural women to make it possible for families to stay in the countryside by transforming the surplus of family production into products suitable for the market.